Tantangan Mengenai Batasan Antara Pekerjaan Dan Kehidupan Pribadi Akibat Tekhnologi Yang Selalu Terkoneksi - Maharani Resti Marinda; Meri Dian Nisa; Luluk Afifah; Choiron Ramdhan; M. Isa Anshori (STIKes Ibnu Sina Ajibarang, 2023)
This study emphasizes the importance of realizing and maintaining work-life balance in today's work environment. This chapter outlines the meaning of this balance, examines how it affects individual well-being and organizational productivity, and explains the factors that influence it. We also discuss ways to achieve better balance in daily routines, including work flexibility, time management, and social support. The digital era has brought significant changes to the way we work and live our daily lives. As technology advances, the concept of work-life balance is becoming increasingly important in both professional and personal lives. This article explains the key challenges individuals face in achieving work-life balance in the digital age, and provides solutions that can help overcome these challenges.